Assessment of the radiant emittance of damaged/contaminated dental light-curing tips by spectrophotometric methods - Abdulrahman A. Balhaddad; Isadora Garcia; Fabrício Collares; Cristopher M. Felix; Nisha Ganesh; Qoot Alkabashi; Ward Massei; Howard Strassler; Mary Anne Melo (Restorative Dentistry & Endodontics)
ObjectivesThis study investigated the effects of physically damaged and resin-contaminated tips on radiant emittance, comparing them with new undamaged, non-contaminated tips using 3 pieces of spectrophotometric laboratory equipment.Materials and MethodsNine tips with damage and/or resin contaminants from actual clinical situations were compared with a new tip without damage or contamination (control group). The radiant emittance was recorded using 3 spectrophotometric methods: a laboratory-grade thermopile, a laboratory-grade integrating sphere, and a portable light collector (checkMARC).ResultsA significant difference between the laboratory-grade thermopile and the laboratory-grade integrating sphere was found when the radiant emittance values of the control or damaged/contaminated tips were investigated (p < 0.05), but both methods were comparable to checkMARC (p > 0.05). Regardless of the method used to quantify the light output, the mean radiant emittance values of the damaged/contaminated tips were significantly lower than those of the control (p < 0.05). The beam profile of the damaged/contaminated tips was less homogeneous than that of the control.ConclusionsDamaged/contaminated tips can reduce the radiant emittance output and the homogeneity of the beam, which may affect the energy delivered to composite restorations. The checkMARC spectrophotometer device can be used in dental offices, as it provided values close to those produced by a laboratory-grade integrated sphere spectrophotometer. Dentists should assess the radiant emittance of their light-curing units to ensure optimal curing in photoactivated, resin-based materials.